?
![\frac{x + 4}{2} - \frac{4}{3} = \frac{3}{2} - \frac{4 - x}{3} \frac{x + 4}{2} - \frac{4}{3} = \frac{3}{2} - \frac{4 - x}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx+%2B+4%7D%7B2%7D++-++%5Cfrac%7B4%7D%7B3%7D++%3D++%5Cfrac%7B3%7D%7B2%7D++-++%5Cfrac%7B4+-+x%7D%7B3%7D+)
Soluções para a tarefa
Respondido por
0
x+4/2-4/3 = 3/2- 4-x/3
2,3,2,3 | 2
1,3,1,3. | 3
1,1,1,1
m.m.c(2,3,2,3)= 2*3=6
3x+12-8= 9-8-2x
3x+2x=9-8+8-12
5x= 9-12
5x= -3
x= -3/5
2,3,2,3 | 2
1,3,1,3. | 3
1,1,1,1
m.m.c(2,3,2,3)= 2*3=6
3x+12-8= 9-8-2x
3x+2x=9-8+8-12
5x= 9-12
5x= -3
x= -3/5
Respondido por
0
(x -4)/2 - 4/3 = 3/2 - (4-x)/3
(x-4)/2 - 4/3 - 3/2 + (4-x)/3 = 0
(3x - 12 - 8 - 9 + 8 - 2x) / 6 = 0
3x - 12 - 8 - 9 + 8 - 2x = 0
x - 12 - 9 = 0
x - 21 = 0
x = 21
(x-4)/2 - 4/3 - 3/2 + (4-x)/3 = 0
(3x - 12 - 8 - 9 + 8 - 2x) / 6 = 0
3x - 12 - 8 - 9 + 8 - 2x = 0
x - 12 - 9 = 0
x - 21 = 0
x = 21
Perguntas interessantes
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Lógica,
1 ano atrás
Matemática,
1 ano atrás